Awareness of the characteristics and applications of ozone gas among students of chemistry in the college of education (Journal of the College of Basic Education, 2022)
The aim of the research is to identify the level of awareness of the characteristics and applications of ozone gas among chemistry students from the College of Education and pure sciences at the University of Baghdad.The research sample used consisted of samples of (112) male and female students out of the total number of (167) studying in day classes and (69) out of (87) students following evening classes during the (2018-2019) academic year. The samples represent (68%) and (79%) of the total number of students from the day and evening classes respectively.To achieve the aim of the research, the two researchers developed a measure of students awareness about the ozone gas and its applications using multiple choice type of test related to (35) issues. The students who were tested required to select between (5) alternative answers in each of these issues.The results were verified for their stability and consistency using Cronbach’s Alpha formula which produced a coefficient score of 0.87.In addition to using Cronbach’s Alpha formula, the results were analyzed statistically using SPSS software including average mean test, Z-test for two independent and unequal samples and Mann-Witney test. During these tests, the researcher used the descriptive analysis approach.The results showed that there is a significance statistical difference at the 0.05 level between the average scores of the level of awareness of students of the day and evening classes equal to (0.0135) in favor of students in day classes. There is also a difference between the average scores of the levels of awareness based on gender equal to (0.025) in favor of female students.The study concluded that the awareness of students in the day and evening classes equals to (64.6%).